2022
DOI: 10.1073/pnas.2122425119
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination of arenes via the degradation of toxic chlorophenols

Abstract: Significance Chlorination reactions are widely applied in organic synthesis, with aryl chlorides being key intermediates in the synthesis of many pharmaceutical products. Here, we demonstrate that waste materials such as chlorophenol pollutants can be valorized as chlorination reagents via catalytic transfer of the chloro group during their mineralization for the generation of valuable aryl chlorides. This process adds value to the destruction of chlorophenol pollutants, and the concept could potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Following C–Cl bond activation, transfer of the chlorine to a substrate, and mineralization of the hydrocarbon component of the waste, must be initiated. Commencing with conditions similar to those reported for the transfer of chlorine atoms in chlorophenol pollutants to arenes 49 , a Cu-catalysed aerobic reaction employing 7,8-benzoquinoline 1a as substrate and PVC (molecular weight, M w : 100,000) as chlorination reagent, led to only trace quantities of the anticipated chlorinated product, namely, 10-chlorobenzoquinoline 1b (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Following C–Cl bond activation, transfer of the chlorine to a substrate, and mineralization of the hydrocarbon component of the waste, must be initiated. Commencing with conditions similar to those reported for the transfer of chlorine atoms in chlorophenol pollutants to arenes 49 , a Cu-catalysed aerobic reaction employing 7,8-benzoquinoline 1a as substrate and PVC (molecular weight, M w : 100,000) as chlorination reagent, led to only trace quantities of the anticipated chlorinated product, namely, 10-chlorobenzoquinoline 1b (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 64%
“…The NaNO 3 promotes the oxidative decomposition of the dechlorinated (hydrocarbon component) polymer/solvent via C=C/C(OH)–C bond activation of the alkene and alkanol intermediates (Supplementary Figs. 27 – 29 ) 43 45 , 49 . In the final step, the PdO catalyses the chlorination of the arene substrate using HCl as the actual chlorination reagent 39 , 42 , 72 .…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative dechlorination of 2,4,6-trichlorophenol to yield a quinone (or related oxidation product) and poly­(2,6-dichlorophenylene oxide) is well documented. Recently, it was reported that under aerobic conditions in the presence of [Cu­(NO 3 ) 2 ] and NaNO 3 , 2,4,6-trichlorophenol can chlorinate arenes via formation of chlorine radicals . Thus, we hypothesize that the Ce­(IV) monoaryloxide chloride 3-Cl 2,4,6 was formed via the oxidation of Ce­(III) by the chlorine radical that was derived from 2,4,6-Cl 3 C 6 H 2 O • .…”
Section: Resultsmentioning
confidence: 87%
“…NO 3 ) 2 ] and NaNO 3 , 2,4,6-trichlorophenol can chlorinate arenes via formation of chlorine radicals 25. Thus, we hypothesize that the Ce(IV) monoaryloxide chloride 3-Cl 2,4,6 was formed via the oxidation of Ce(III) by the chlorine radical that was derived from 2,4,6-Cl 3 C 6 H 2 O • .…”
mentioning
confidence: 94%
See 1 more Smart Citation